STRATEGI PENGUATAN KELEMBAGAAN KELOMPOK TANI PADA USAHATANI JAGUNG PIPILAN DESA PENYANDINGAN KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU (JASEP, 2019)
Strategy for Institutional Strengthening of Farmer Group in Pipilan Maize Farming District of Sosoh Buay Rayap Sub District Ogan Komering Ulu Regency. Method research this is survey method. P lamb lan until l use meto de random plated balanced (proportionate random sampling), samples taken that is group farmers . Data type used in research this including data primary and secondary . Data processing method using SWOT Matrix Analysis. Where SWOT Matrix is a combination of IFAS and EFAS factors so as to form a strategic i. Unknown internal factors such as the strength (m emiliki closeness relationship fellow member groups , in the sale of crops and k Quality of results jagu ng good ) and weakness (t ingkat education member group still low , k urangnya fund in development farming and technology still traditional). And external ie opportunities (a funder sadrodi harvest system, the training by PPL and market demand for corn is high enough), and threats (land for maize farming owned by the government , the existence of pest and weak cooperation in group organizing). And strategy of institutional strengthening of farmer group that is SO strategy (m retain trust of the investors' distributors saprodi that has been there to help in activities keep working corn pipilan, mingkatkan results production be more good again . and Adding and maintain quality corn to be able meet demand market), ST strategy (m retain land as management farming corn into majority income mainstay society for the government still give permission land for used , enhanced control in prevention attack pest on farming corn and m embangun cooperation in do activities keep working corn to be organized with good), s strategy W O ( optimalization cooperation between member group in capital for improve amount production corn , m take advantage of training extension of existing use for add insight and knowledge for member groups and m seupayakan existence machine drying for quality corn sign in in standardization ), and strategy WT (m engadakan mentoring program and counseling on routine accompanied with demonstration so could improve ability member group farming , doing activities prevention from pests that attack use stun battery is glued in around fence use minimize spending funds and m emperkuat organizing group with regulation stewardship on futures and cooperate for submission help form